Photopolymerization performed under dark conditions using long-stored electrons in carbon nitride. Issue 7 (18th May 2021) - Chen, Guang; Zhang, Zidan; Zhang, Wenjian; Xia, Lei; Nie, Xuan; Huang, Weiqiang; Wang, Xiaoqian; Wang, Longhai; Hong, Chunyan; Zhang, Ze; You, Yezi
Abstract : Protonated cyano-modified carbon nitride was synthesized, and it could store photoelectrons with a lifetime of one month. The stored electrons could drive polymerization in the dark and avoid photodegradation compared to direct photopolymerization. Abstract : In nature, the chemical energy and electrons stored in ATP and NADPH generated during irradiation can facilitate biochemical reactions under dark conditions. However, in artificial photoreaction systems, it is still very difficult to perform photoreactions under dark conditions due to the fact that the photogenerated charge pairs can recombine immediately upon ceasing the irradiation. Preventing the recombination of photogenerated charge pairs still constitutes a major challenge at present. Here, it is reported that functionalized carbon nitride nanomaterials having many heptazine rings with a positive charge distribution, which can tightly trap photogenerated electrons, efficiently prevent the recombination of photogenerated charges. These stored charges are exceedingly long-lived (up to months) and can drive photopolymerization without light irradiation, even after one month. The system introduced here demonstrates a new approach for storing light energy as long-lived radicals, enabling photoreactions under dark conditions.